Depletion of Mycobacterium tuberculosis transmembrane protein Rv3737 reduces pathogen survival and induces M1 macrophage polarization against tuberculosis - Peng, Zhangli; Xu, Chao; You, Taixian; Shu, Chengjie; Li, Qing; Li, Nana; He, Renzhong; Chen, Ling; Xu, Lin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesMycobacterium tuberculosis (Mtb) modulates macrophage polarization to evade host immunity and enhance intracellular survival. Rv3737, a probable conserved transmembrane protein in Mtb, has an unclear biological function. This study investigates the role of Rv3737 in regulating macrophage polarization and Mtb survival within host cells.MethodsThe structure of Rv3737 was predicted using bioinformatics tools. Macrophage polarization markers were assessed by real-time PCR for M1/M2-associated cytokines, and flow cytometry for CD86+/CD206+ expression. RNA sequencing, along with KEGG and GO analyses, was used to explore underlying regulatory pathways. Western blotting evaluated the phosphorylation status of NF-κB (P65, IκB) and MAPK (ERK, P38, JNK) signaling components. Colony-forming units (CFUs) and inducible nitric oxide synthase (iNOS) levels were examined in H37RvΔRv3737-infected macrophages pretreated with specific inhibitors (JSH-23, U0126-EtOH, SB203580, SP600125).ResultsRv3737 is predicted to contain 10 transmembrane segments enriched in aliphatic amino acids. Deletion of Rv3737 in H37Rv (H37RvΔRv3737) led to upregulation of M1 markers (TNF-α, IL-1β, IL-6, iNOS, MCP-1, CD86) and downregulation of M2 markers (Arg-1, IL-10, TGF-β, CD206). Conversely, overexpression of Rv3737 (MS_Rv3737) promoted M2 polarization. RNA sequencing indicated NF-κB pathway activation in macrophages infected with H37RvΔRv3737, along with increased phosphorylation of P65, IκB, ERK, and P38. Inhibition of NF-κB (with JSH-23) and P38 MAPK (with SB203580) reduced iNOS levels and partially restored Mtb survival, indicating that Rv3737 deletion enhances the macrophage antimicrobial response.ConclusionsRv3737 suppresses M1 macrophage polarization to promote Mtb survival. Its deletion enhances host antimicrobial activity by activating NF-κB and MAPK signaling pathways. Targeting Rv3737 may represent a novel strategy for tuberculosis therapy.